UPAYA GURU DALAM MELATIH KEMANDIRIAN ANAK USIA DINI - Atalia; Dewi Ferawati; Asyruni Multahada (Fakultas Tarbiyah Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
The purpose of this research is to reveal about: Teachers' efforts in training early childhood independence, supporting and inhibiting factors in the process of early childhood independence education This research was conducted using a qualitative approach with descriptive research type. The data sources used were teachers, children and school principals. Data collection techniques by interview, observation and documentation. The results showed that the teacher can improve the child's overall independence so that students can become independent children, namely children who can carry out their own activities, are able to socialize, show empathy, and can make decisions with actions, prepare RPPH (Daily Learning Implementation Plan) , integrating independent learning with children's learning activities, creating a conducive and attractive learning atmosphere, and teachers always providing concrete examples in every activity. Supporting and inhibiting factors in the process of early childhood independence education, namely: a. Supporting factors Referring to the 2013 curriculum, PAUD teachers are very enthusiastic about indicators that are in accordance with the needs and development of children, very high enthusiasm and awareness of teachers, adequate facilities and infrastructure and b. The inhibiting factors for parents who are overprotective or spoil their children, and the lack of teachers in the classroom, the existing teachers do not match the ratio of the number of students.